1980
DOI: 10.1073/pnas.77.1.675
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive action of parathyroid hormone preparations on rats and dogs.

Abstract: Bovine parathyroid extract and two commercial preparations containing the first 34 amino acids of synthetic bovine parathyroid hormone [bPTH41-34)] produced dose-related hypotension in anesthetized rats. Dogs were 10 times more sensitive to the two bPTH41-34) preparations than were rats.Propranolol, phentolamine, atropine, and promethazine did not affect the hypotensive action of bPTH-1-34) in rats and dogs. bPTH-1-34) decreased perfusion pressure in rat hindlimbs perfused in situ with Ringer's solution and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0
2

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(45 citation statements)
references
References 5 publications
4
39
0
2
Order By: Relevance
“…In the present study a potential role of vasodepressor hormones such as the prostaglandins 31 and parathyroid hormone 32 in attenuating the hypertensive response to acute hypercalcemia was also investigated. In rats pretreated with the cyclooxygenase inhibitor indomethacin the hypertensive response to acute hypercalcemia was not altered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study a potential role of vasodepressor hormones such as the prostaglandins 31 and parathyroid hormone 32 in attenuating the hypertensive response to acute hypercalcemia was also investigated. In rats pretreated with the cyclooxygenase inhibitor indomethacin the hypertensive response to acute hypercalcemia was not altered.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, vasodilative hormones such as prostaglandins 31 and parathyroid hormone 32 could attenuate the pressor response to acute hypercalcemia. In this respect, recent studies have shown that calcium enhances prostaglandin synthesis.…”
mentioning
confidence: 99%
“…The known effect of the single doses of 1-34 PTH (Pang et al 1980, Saglikes et al 1985, Baksi 1988 or 1-84 PTH (Saglikes et al 1985) is the activity that transiently decreases blood pressure in intact (Pang et al 1980, Saglikes et al 1985 or thyroparathyroidectomized (Baksi 1988) animals. In these experiments, the decrease in blood pressure was observed immediately, within about 1 min, after PTH injection.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have not demonstrated such elevations in hypertensive subjects (7). Acute administration of PTH results in decreased blood pressure (27) and relaxation of vascular tissue (28), suggesting that PTH is a direct vasodilator. By contrast, long-term attenuation of PTH by parathyroidectomy prevents the normal age-related increases in blood pressure in hypertensive and normotensive animals (29).…”
Section: Fig 4 Correlation Between Serum Intact Parathyroid Hormonementioning
confidence: 99%